The Oxford illustrated history of science - Iwan Rhys Morus; Morus, Iwan Rhys (Oxford Oxford University Press, 2017)
The Oxford Illustrated History of Science offers readers an accessible and entertaining introduction to the history of science as well as a valuable and authoritative reference work.--
Part 1. Seeking origins -- Science in the ancient Mediterranean world / James Evans -- Science in ancient China / Donald Harper -- Science in the medieval Christian and Islamic worlds / Steven J. Livesey and Sonja Brentjes -- Science in the pre-modern east / Dagmar Schaefer -- The scientific revolution / John Henry -- Enlightenment science / Jan Golinski. -- Part 2. Doing science. -- Experimental cultures / Iwan Rhys Morus -- Exploring nature / Amanda Rees -- The meaning of life / Peter Bowler -- Mapping the universe / Robert Smith -- Theoretical visions / Matthew Stanley -- Communicating science / Charlotte Sleigh.
Includes bibliographical references (pages 411-422) and index.
Keywords: Science; Science